COMMUNICATION IN BRIEFING ON DEPARTMENT FOOD AND BEVERAGE SERVICE HOTEL NOVOTEL PEKANBARU - Muhammad Afiky Afnan; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Briefing activities are needed by a company that has a high work ethic in order to facilitate and motivate employees to work. Therefore, this study aims to describe the communication elements in briefing at the food and beverage service of the Novotel Pekanbaru. The research used a qualitative descriptive method to analyze based on data analysis techniques such as observation, interview, and documentation. Communication in direction includes elements of people, message, Media, Effect, and feedback. Based on the results of the research that has been carried out, the total results of observations and interview, it can be concluded that the Communication in Briefing at the Food and Beverage service of Novotel Pekanbaru has not been running smoothlyKeywords: Hotel, Food and Beverage Service, Briefing, Communication